Exploring the views of Singapore junior doctors on medical curricula for the digital age: A case study. - Humairah Zainal; Xin Xiaohui; Julian Thumboo; Fong Kok Yong (PLoS ONE, 2023)
This study aims to explore the perspectives of medical trainees on the impartation of digital competencies in Singapore's medical school curricula. It also considers how the medical school experience can be strengthened in order to bridge potential gaps in the integration of these competencies in the local curricula. Findings were drawn from individual interviews with 44 junior doctors from Singapore's public healthcare institutions including hospitals and national specialty centers. House officers and residents from different medical and surgical specialties were recruited using purposive sampling. Data was interpreted using qualitative thematic analysis. The doctors were in their first to tenth year of post-graduate training. Thirty of them graduated from the three local medical schools whereas 14 others were trained overseas. Overall, they felt insufficiently prepared to utilize digital technologies in view of their limited exposure to such technologies in medical school. Six key reasons were identified: lack of flexibility and dynamism within the curriculum, dated learning style, limited access to electronic health records, gradual uptake of digital technologies in the healthcare sector, lack of an ecosystem that promotes innovation, and lack of guidance from qualified and available mentors. Equipping medical students with skills relevant to the digital age would benefit from a concerted effort from multiple stakeholders: medical schools, medical educators and innovators, as well as the government. This study bears important implications for countries that seek to bridge the 'transformation gap' brought about by the digital age, which is defined as the sharp divergence between innovations that healthcare providers recognize as important but for which they feel insufficiently prepared.